Clinical and epidemiological spectrum of coronavirus disease 2019 in Central Kerala: a retrospective case series - Thomas, Ronnie; John, Bins M.; Koothapally, Joe Thomas; Kumar, Sanjeev; Adiody, Supriya; Balachandran, Venu; Valsan, Chithra; Kuttichira, Praveenlal (International Journal Of Community Medicine And Public Health, 2021)
Kerala state in India was known for its early response to the Covid-19 pandemic by public health mitigation measures through science-based advocacy. The objective of this study was to analyze epidemiological and clinical characteristics of COVID-19 patients admitted to a tertiary care center in central Kerala. This retrospective case series was undertaken by reviewing the medical records and extracting the epidemiological data, clinical symptoms and laboratory findings of consecutive patients admitted between April 1st and September 31, 2020. Clinical and demographic parameters of hospitalized patients were analyzed regarding their association with the severity of disease. The mean age of the patients was 35.8 years with significant male predominance. Shopkeepers represented 15.6% of the patients and healthcare workers represented 12.5%. Primary contact with a known case was documented in 62.5% of the patients. Asymptomatic patients constituted 25% of the patients and the most commonly experienced symptoms were fever, cough, breathlessness and diarrhea. Three patients had atypical presentations in the form of generalized seizures, intussusception and generalized anxiety with suicidal ideation. Neutrophilia and Lymphopenia were the most dominant laboratory finding. The clinical spectrum of COVID-19 in the study population is wider than previously described in literature.